Alcohol and sleep disturbances - I. S. Efremov; A. R. Asadullin; R. F. Nasyrova; E. A. Akhmetova; E. M. Krupitsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
This article presents a non-systematic descriptive review of sleep disturbance problems in patients with alcohol dependence. A search was carried out in databases such as Google Scholar, ELibrary.ru, Scopus, PubMed. We considered works published no earlier than January 1, 2015, but no later than January 10, 2020. A search was carried out with the use of search queries of various combinations of the specified words: “alcohol use disorder,” “alcoholism”, “insomnia,” and others. After analyzing a number of publications, it is possible to conclude that the relationship between the described phenomena is synergetic with a mutual reinforcement. In the current review it is demonstrated that the risk of the development of alcoholism against the background of sleep disturbances might be related to the initial use of alcohol as a somnolent with further development of tolerance and alcoholism. At the same time, the severity of sleep disturbances quite often coincides with the severity of alcohol dependence. For those patients who are in a stage of remission sleep disturbances is a risk factor for relapse. This review clearly demonstrates that further research of the relationships between alcohol dependence and sleep disorders are needed.